Effect of filler's type, content and mixing method on properties of low density polyethylene/natural rubber (LDPE/NR) composites - Mohamed Erfieda, Abdulbaset (School of Materials Engineering, 2011)
This study was based on preparation of low density polyethylene (LDPE) and natural rubber (NR) composites with three types of fillers (Silica, Corn Starch and Coconut Husk) and different contents (10, 20 and 30 phr) using three different mixing methods. The objectives of research are to investigate the effect of filler to polymers composite in NR/LDPE composites which to measure filler content in each phase.